Meaning and coping orientation of bereaved parents: Individual and dyadic processes - Albuquerque, Sara (PLoS One, 2017)
The present study aimed to examine whether bereaved parents “meaning-made”–defined as results of attempts to reduce discrepancies between the meaning assigned to the death of the child and self and world-views—was influenced by their own and their partner’s coping orientations. Coping orientations were conceptualized within the Dual Process Model, which entails loss coping orientation (LO; focus on the loss itself), restoration coping orientations (RO; focus on stressors that come about as an indirect consequence of the bereavement), and a flexible oscillation between both coping orientations. The sample consisted of 227 couples identified through obituary notices in local and national newspapers, who provided data at 6, 13, and 20 months after the death of their child. At all three points of measurement, both partners independently completed the Dual Coping Inventory (DCI) and a scale developed by the authors about meaning-made from the loss. Data were analyzed using a multi-level Actor-Partner Interdependence Model. Results show that the combination of parents’ own LO and RO (operationalized through the interaction effect between LO and RO) have a positive effect in parents’ meaning-made. Partners’ LO have a negative effect in parents’ meaning-made. These results highlight the importance of, in the context of parental bereavement, being flexible by using both coping orientations, and of acknowledging the interdependence between partners, namely, the interpersonal process by which partner’s coping affect one’s meaning-made.